The Polish United Workers’ Party (PZPR) in October 1956 and during the elections of January 1957 in Cracow Voivodeship - Drabik, Sebastian (Pamięć i Sprawiedliwość, 2011)
The time of the PRL’s political thaw began on a greater scale in December 1954. At the beginning of 1956, the Twentieth Congress of the Communist Party of the Soviet Union acted as a catalyst for change not only in Poland but also in Hungary. However, the 1956 events in Poland reached their climax in the autumn. At the end of a dramatic meeting held between 19 and 21 October, the Seventh Plenum of PZPR Central Committee (during which Soviet delegation with Khrushchev came to Poland) on 21 October 1956 elected new members of the Politburo (the Political Bureau of the Polish United Workers’ Party) with its First Secretary – Władysław Gomułka. The turning point in the activity of the Communist Party in Cracow was the Plenum of PZPR Voivoidship Committee on 25-27 October 1956 in Cracow. At this point, it is worth mentioning that a group of youth organizations members, having affiliations with the party, played a significant role in political revival in Cracow. Among its leaders there were: Stefan Bratkowski, his brother Andrzej, as well as Bernard Tejkowski and Janusz Ogorzałek. The most important moment was an election of the new authorities. 43 persons (out of 45 members of the Voivodeship Committee plenum) took part in decisive vote for members of the Voivodeship Committee Executive finally electing: B. Drobner, S. Filipiak, T. Hankiewicz, W. Kozub, S. Krzakiewicz, M. Kieta, W. Machejek, J. Nagórzański, S. Pięta, B. Tejkowski, M. Waldenberg. In effect, the position of the majority of hitherto party leaders strengthened. During few months after the Polish thaw, the new Executive was a decision-making body of the Cracow’s PZPR. Drobner became a new Party leader in the Voivodeship, followed by Lucjan Motyka in February 1957. Between the autumn of 1956 and the spring of 1957 the Party was deeply engaged in preparation for the elections. Despite of its efforts, the turnout was the lowest in the country and the PZPR’s candidate – Jan Antoniszczak did not get an electoral mandate, therefore, a byelection in his constituency was necessary. During and after the election campaign an internal dispute in Executive erupted. A number of independent activists occurred in the region and the members of the former PSL (The Polish People’s Party) became active. In the course of time, the situation was finally under control and all dissidents such as Waldenberg were removed from the authority’s circle and from the party. Then another dispute arose over the problem of the employment of the former functionaries of the security apparatus and of the Security Office (remaining active before 1956). After the elections, Motyka’s people established new party authorities in Cracow’s Voivodeship which held their position within the next decade.